Evaluation of hybrid problem-based learning in large classrooms: a qualitative and quantitative analysis - Kharay, Sonia S.; Sharma, Anu; Bansal, Priya (International Journal of Research in Medical Sciences, 2018)
Background: Problem Based Learning (PBL) for teaching preclinical sciences has been proposed in curricular reform by Medical Council of India. PBL is a student-centred approach, enabling deep and transformative student learning. A ’hybrid’ approach to PBL uses a range of class-based teaching methods; delivering a mode of PBL which is less resource intensive and more flexible than ‘pure’ PBL. In hybrid PBL, problems are solved in groups, but lectures are used to present the fundamental concepts and difficult topics. Our institution follows a traditional lecture-based curriculum. The present cohort study was undertaken to determine student and faculty perceptions for hybrid PBL as well as impact on student engagement. Methods: Hybrid PBL method was implemented for one cohort of hundred first year medical students. Previous batch was used as control taught by traditional lecture-based curriculum alone. Methodological triangulation design was employed for impact of hybrid PBL on student engagement (attendance scores-Chi square) and student and faculty perception to hybrid PBL (reflections- grounded theory) Results: The mean attendance score of MBBS batch 2016 was significantly better than batch 2015 (p=0.0001). The emerging themes in student reflections were innovative method, collaborative learning, quest for knowledge, promote long term retention and links to real-life scenario. Acquisition of soft skills (social and moral responsibility) was novel emerging theme in student reflections. Active student participation and improved critical thinking were themes expressed in faculty perceptions. Conclusions: Hybrid PBL with small groups is successful in large classrooms. Introduced at the initial phase of undergraduate medical education, it can assist robust self-appraisal in students and strengthen soft skills.